The Implementation of Student Admission Based on Zoning in Indonesia : Problems, Challenges, and Solutions - Ardi Ardi; Muhammad Danil; Dewi Murni; Nurhizrah Gistituati; Rusdinal Rusdinal; Fauziah Hervi (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This research aims to analyze the problems that arise when implementing zoning as a method of student admission and find possible solutions. This study used the systematic literature review method with a qualitative approach. The data collection method used was documentation, namely examining documents in the form of books, literature, and scientific journals related to the topics written in this journal. Data was collected from reviewing the official website of eric.gov, Sinta, Scopus, and Garuda. Data were analyzed using thematic analysis techniques. The result of the study showed some of the main problems in implementing zoning-based admissions. These include the problem of establishing fair and equitable zoning boundaries, enrollment procedures that often need to be more transparent, the accumulation of students in good schools in the zone, and the need for more awareness and active participation from parents. Several solutions can be considered to address these issues. Such as increased investment in education infrastructure development by the government and the implementation of a strict monitoring system for the admission process based on zoning, and the government also needs to strengthen schools in vulnerable zone areas with various quality and facility improvement programs. This policy will help provide a more inclusive and high-quality education for all students by analyzing and addressing the issues that arise when implementing zoning-based admissions.